Mapping the Landscape of Islamic Business Ethics Research in Indonesian SINTA-Indexed Journals: A Bibliometric Analysis - Sofyan, Andi Syathir; Rafika; Sofyan, Syaakir (Lead Journal of Economy and Administration, 2025)
This study aims to see the development of trends in the study of Islamic business ethics in the scope of business and management published in Sinta-indexed journals. This study uses a bibliometric method with the R Studio analysis tool which is used to analyze the bibliographic data obtained automatically. The results of the bibliometric analysis found that Islamic business ethics research is dominated by Islamic business ethics and ethic which uses more quantitative approaches. Furthermore, some of the research themes that can develop in the future are themes related to the Islamic Business Ethics Issue and the Customer Satisfaction Issue. This research contributes to future research and provides scientific novelty in the assessment of Islamic business ethics publications in the scope of business and management and is also practically and theoretically very important for academics.